Outcome Evidencing and Impact Estimation: Rising Demand and Need for Nutritious Food for both Current and Future Generations (Challenge 5) - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
A key global challenge of our times is how to feed and nourish a growing population while minimizing the impact on the environment, against a backdrop of persistent rural poverty and rising levels of (absolute) inequality. The CGIAR’s Research Program on Forests, Trees, and Agroforestry (FTA) undertook significant work—both research and scaling related—to address this challenge. Being one of five main global challenges addressed by FTA, we refer to it as Challenge 5: Rising demand and need for nutritious food for both current and future generations. The purpose of this report is to present the findings of our review of this work.